Temporal Information Systems in Medicine - Combi, Carlo; Keravnou-Papailiou, Elpida; Shahar, Yuval; SpringerLink (Online service) (Boston, MA : Springer US, 2010)
The effective and efficient use of information systems in health care organizations and services is a vital element of the quality of life worldwide. The modeling of time has attracted interest from a number of research communities, each addressing aspects from its specific sphere of interests. The database systems community is interested in how to store, maintain, and query time-oriented data. The Artificial Intelligence (AI) community is interested in formal theories of time, temporal logics, temporal constraints and temporal reasoning techniques. The Artificial Intelligence in Medicine (AIM) community is interested in the broader issues involved in reasoning about time-oriented data: in particular, the implications of temporal reasoning on clinical tasks such as diagnosis, monitoring, and longitudinal guideline-based care. Temporal Information Systems in Medicine introduces the engineering of information systems for medically-related problems and applications. The chapters are organized into four parts; fundamentals, temporal reasoning & maintenance in medicine, time in clinical tasks, and the display of time-oriented clinical information. The chapters are self-contained with pointers to other relevant chapters or sections in this book when necessary. Time is of central importance and is a key component of the engineering process for information systems. About this book: Presents a cutting edge text on Temporal Information Systems in Medicine. Chapters are self contained with pointers to other relevant material or chapters in this book. Serves as an introduction to a reader interested in a general theoretical understanding of temporal representation and reasoning, especially as it relates to medicine, and as a source for those interested in specific clinical time-oriented tasks, such as diagnosis or abstraction of clinical records. This book is designed as a secondary text or reference book for upper -undergraduate level students and graduate level students concentrating on computer science, biomedicine and engineering. Industry professionals and researchers working in health care management, information systems in medicine, medical informatics, database management and AI will also find this book a valuable asset.
The role of Time in Medicine -- Fundamentals -- Temporal Modeling and Temporal Reasoning -- Temporal Databases -- Temporal Reasoning and Maintenance in Medicine -- Temporal Clinical Databases -- Abstraction of Time-Oriented Clinical Data -- Time in Clinical Tasks -- Time in Clinical Diagnosis -- Automated Support to Clinical Guidelines and Care Plans -- The Display of Time-Oriented Clinical Information -- Displaying Time-Oriented Clinical Data and Knowledge.
Keywords: Computer science; Database management; Information systems; Artificial intelligence; Computer vision; Biomedical engineering; Computer Science; Information Systems Applications (incl.Internet).; Database Management; Artificial Intelligence (incl. Robotics).; Biomedical Engineering; Models and Principles; Computer Imaging, Vision, Pattern Recognition and Graphics